Goal Missed, Self Hit: Goal-Setting, Goal-Failure, and Their Affective, Motivational, and Behavioral Consequences - Höpfner, Jessica; Keith, Nina (Frontiers in Psychology, 2021)
Setting high and specific goals is one of the best-established management tools to increase performance and motivation. However, in recent years, potential downsides of goal-setting are being discussed. One possible downside is the high risk of failing the goal. In an approach to integrate research on the consequences of goal-failure and the basic assumptions of goal-setting theory, we investigated whether failure of a high and specific goal has detrimental effects on a person’s affect, self-esteem, and motivation. In Experiment 1, 185 participants received fictitious feedback about attaining or failing an assigned high and specific goal. In Experiment 2 with 86 participants, we manipulated goal-failure through task-difficulty and we included task choice as a behavioral measure of motivation. In both experiments, participants who failed the high and specific goal showed a decrease in affect, self-esteem, and motivation compared to participants who attained that goal. Results indicate that failing a high and specific goal can be damaging for self-related factors that may be crucial for organizational long-term outcomes. We advise organizations to consider potential undesirable effects when using goal-setting interventions.